The Epigenetic Cytocrin Pathway to the Nucleus. Epigenetic Factors, Epigenetic Mediators, and Epigenetic Traits. A Biochemist Perspective - Navarro, Gemma; Franco, Nuria; Martínez-Pinilla, Eva; Franco, Rafael (Frontiers in Genetics, 2017)
A single word, Epigenetics, underlies one exciting subject in today’s Science, with different sides and with interactions with philosophy. The apparent trivial description includes everything in between genotype and phenotype that occurs for a given unique DNA sequence/genome. This Perspective article first presents an historical overview and the reasons for the lack of consensus in the field, which derives from different interpretations of the also diverse operative definitions of Epigenetics. In an attempt to reconcile the different views, we propose a novel concept, the “cytocrin system”. Secondly, the article questions the inheritability requirement and makes emphasis in the epigenetic mechanisms, known or to be discovered, that provide hope for combating human diseases. Hopes in cancer are at present in deep need of deciphering mechanisms to support ad hoc therapeutic approaches. Better perspectives are for diseases of the central nervous system, in particular to combat neurodegeneration and/or cognitive deficits in Alzheimer’s disease. Neurons are post-mitotic cells and, therefore, epigenetic targets to prevent neurodegeneration should operate in non-dividing diseased cells. Accordingly, epigenetic-based human therapy may not need to count much on transmissible potential.